Size and volatility of particle emissions from an ethanol-fueled HCCI engine. Issue 5 (4th May 2017) - Swanson, Jacob J.; Franklin, Luke M.; Bika, Anil S.; Kittelson, David B.
ABSTRACT: A scanning mobility particle sizer was used to determine the size, number, and mass concentration of particle emissions from an ethanol-fueled homogeneous charge compression ignition (HCCI) engine. Semi-volatile particle composition was characterized using tandem differential mobility analysis (TDMA). Variable temperature thermal conditioning was used to gain insight into particle volatility and a catalytic stripper was used to determine the solid particle distribution. Four engine conditions were evaluated, including low to moderate range loads and motoring (deceleration, coasting). Results indicated that aerosol from a fully premixed HCCI engine under firing conditions is formed almost entirely via nucleation of semi-volatile material originating from the lubricating oil. TDMA analysis indicated 98% of total particle volume evaporated below 100°C. Results pointed towards homogeneous nucleation of precursors derived from the organic species in the lubricating oil, possibly in combination with a sulfur species. The motoring condition, with no fuel injected, exhibited the highest number and mass concentrations. During motoring, there was poor sealing leading to increased atomization of oil and associated ash emissions. Emissions were lower during firing with better sealing and much less atomization, but evaporation of the most volatile fractions of the lubricating oil still led to significant PM emissions consisting of nearly entirely semi-volatile particles containing very little ash. © 2017 American Association for Aerosol Research